Causal effects of B vitamins and homocysteine on obesity and musculoskeletal diseases: A Mendelian randomization study - Fu, Liwan; Wang, Yuquan; Hu, Yue-Qing (Frontiers in Nutrition, 2022)
Objectives: Although homocysteine (Hcy) increases the risk of cardiovascular diseases, whether Hcy affects fat and musculoskeletal diseases is less clear. We performed a Mendelian randomization study to estimate the associations of Hcy and B vitamins concentrations with fat and musculoskeletal relevant diseases in the general population. Methods: We selected independent single nucleotide polymorphisms of Hcy (n = 44,147), vitamin B12 (n = 45,576), vitamin B6 (n = 1864), and folate (n = 37,465) at the genome-wide significance level as instruments and applied them to the studies of summary-level data for fat and musculoskeletal phenotypes from the UK Biobank study (n = 331,117), the FinnGen consortium (n = 218,792), and other consortia. Two-sample Mendelian randomization (MR) approaches were utilized in this study. The inverse variance weighting (IVW) was adopted as the main analysis. MR-PRESSO, MR-Egger, weighted median estimate, bidirectional MR and Multivariable MR were performed as sensitivity methods. Results: Higher Hcy concentrations were robustly associated with the increased risk of knee osteoarthritis (odds ratio (OR) 1.119; 95% confidence interval (CI) 1.032 to 1.214; P = 0.007), hospital diagnosed osteoarthritis (OR 1.178; 95%CI 1.012 to 1.37; P = 0.034), osteoporosis with pathological fracture (OR 1.597; 95%CI 1.036 to 2.46; P = 0.034) and soft tissue disorder (OR 1.069; 95%CI 1.001 to 1.141; P = 0.045) via inverse variance weighting method and other MR approaches. Higher vitamin B12 levels were robustly associated with decreased body fat percentage and its subtypes (all P < 0.05). Bidirectional analyses showed no reverse causation. Multivariable MR analyses and other sensitivity analyses showed directionally similar results. Conclusions: There exist significant causal effects of vitamin B12 in the serum and Hcy in the blood on fat and musculoskeletal diseases, respectively. These findings may have an important insight into pathogenesis and possible future therapies of fat and musculoskeletal diseases.